10.61533 PENERAPAN GREEN ACCOUNTING BERDASARKAN TRIPLE BOTTOM LINE THEORY UNTUK MENDUKUNG SUSTAINABILITY DEVELOPMENT (STUDI PADA PT TIMAH TBK PANGKALPINANG) - Felix; Hendarti Tri Setyo Mulyani; Rizal R. Manullang (Jurnal Ilmiah Niaga Bisnis Elektronik, 2026)
This study aims to analyze the application of Green Accounting based on the Triple Bottom Line Theory in supporting sustainable development at PT Timah Tbk Pangkalpinang. Data collection techniques include interviews, observation, and documentation conducted within the HSE & Sustainability Division and the Finance Department, using a qualitative research method. The results indicate that the implementation of Triple Bottom Line-based Green Accounting plays an important role in supporting sustainable development at PT Timah Tbk. However, there are still several challenges in optimizing sustainability reporting and increasing environmental awareness more broadly. This research recommends that the company continue to improve transparency and accountability in environmental reporting and become more active in involving stakeholders in decision-making processes related to sustainability. This will strengthen social legitimacy while ensuring long-term business and environmental sustainability.